PENGGUNAAN CELEBRITY ENDORSER DAN FAKTOR-FAKTOR YANG HARUS DIPERTIMBANGKAN DALAM PEMILIHAN ENDORSER (Fokus Ekonomi, 2011)
Using celebrity endorser for communicating a product has been increasing over the pastyears. It has more advantages rather than using non-celebrity endorser. Marketers obviouslyacknowledge the power of celebrities in influencing consumer-purchasing decisions. Any brandcan get a celebrity easily, but getting a celebrity consistent with the right brand, to the rightdegree, at the right time, for the right purpose and in the right way is not easy. Celebrityendorsement if used effectively will make good advantage in communicating the brand andaffecting buying behavior of the customer. However, using celebrity as endorser still has risk. Thispaper, from literature survey, results some factors to consider in using celebrity endorsement.Key words: endorser, celebrity, brand